Politik Identitas Agama - Sukri Ali (Jurnal Ilmiah Wahana Pendidikan, 2020)
Issue of religion or religious politicization use in Morotai from the perspective of the reasonable circumstantial performed by elite politics, because of religious politicization issues on Morotai elections seen can destroy the presence voters in determining political options in accordance with prospective with the candidate in the same religious and ideological. Construction of religious-based identity politics issues considered may have benefits and a chance to win the election in the electoral District of Morotai Island. While aspects of interactional and communication can be concluded, that the political message blend religion and patterns of communication that uses religion as a source of the identity of the candidates can make the candidate build of misunderstanding with voters. In addition, religious politicization issues in the elections, it can be concluded that the Morotai candidates or young candidates in conducting socialization with voters feeling they in the same faith and religion. This situation is reinforced by the pattern of public relations of Morotai which still are paternalistic. The pattern of these relationships increasingly thick supported by a majority of the voters’ education level is still low and living in the village-rural. The result of the pattern of public relations as it was then the community that chooses the Regent and Vice Regent of emotional closeness will be up to voters with candidates. Whereas the community is needed in determining political rights in choosing the leader not because of emotional closeness or with prospective partners, but to choose the leader who has the vision, as well as a good program. In this jurnal, using writing research, because we use this method according to the author more profound understanding and explaining religious politic on Morotai. While the theory that the authors use as a knife, the theory is analyses of religious politicization, elite theory, and elections.